Entrepreneurship : strategies and policies - Amedzro St-Hilaire, Walter (Oakville, ON ; Palm Bay, Florida : Apple Academic Press Inc., 2020)
c
Have the entrepreneurship policies adapted to its business context? -- Is the contemporary business pact in an unfinished transition? -- What are the stimulating measures for entrepreneurship? -- Prospects for effective entrepreneurship -- The challenges of the evaluation of the regulation of enterprises -- Salary trajectories that are growing in enterprises -- Role of growth, productivity, and added value -- The challenges of a new managerial model for entrepreneurship -- Is the distribution of added value more and more anti-growth? -- Entrepreneurship governance, less and less respectful of work -- Towards a reallocation of added value to growth and the relaunch of the social contract? -- How to find a new balance between autonomy and security for employees -- Rebalancing the entrepreneurship governance -- Towards parity for the entrepreneurship governance -- How to better integrate the specificity of enterprises into public orders?
OCLC-licensed vendor bibliographic record.
Keywords: Entrepreneurship; BUSINESS & ECONOMICS / Industrial Management; BUSINESS & ECONOMICS / Management; BUSINESS & ECONOMICS / Management Science; BUSINESS & ECONOMICS / Organizational Behavior; BUSINESS & ECONOMICS / Entrepreneurship